The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1757-899x/726/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life of thermoset composite materials

Abstract: This article deals with the lifetime of laminated materials produced by different production technologies (hand lamination technology, vacuum bagging technology and prepreg technology with curing in the oven) during cyclic repeated bending stress. Like tested materials composite systems were chosen composite systems with epoxy matrix and carbon reinforcement (Kordcarbon CC200T, epoxy resin with trade name L285) and second composite epoxy system with glass reinforcement (Quadra-axial glass fabric, named Saertex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…They concluded that during the high-load application, the damage tends to be dominated by fiber properties, while during low-applied load, the damage is dominated by matrix properties. Another test of glass-reinforced thermoset was carried out by Zaludek et al [26], in which the thermoset was subjected to a bending load corresponding to 80% of its tensile strength. Studies have shown that glass-reinforced plastic can withstand a considerable number of cycles, namely more than 30,000 cycles, even at such a high load.…”
Section: Fatigue Analysismentioning
confidence: 99%
“…They concluded that during the high-load application, the damage tends to be dominated by fiber properties, while during low-applied load, the damage is dominated by matrix properties. Another test of glass-reinforced thermoset was carried out by Zaludek et al [26], in which the thermoset was subjected to a bending load corresponding to 80% of its tensile strength. Studies have shown that glass-reinforced plastic can withstand a considerable number of cycles, namely more than 30,000 cycles, even at such a high load.…”
Section: Fatigue Analysismentioning
confidence: 99%
“…Figure 5. Comparison of the fatigue behavior of composites (left)[44] and failure diagram of carbon fiber-epoxy with regard to water content (right)[45] …”
mentioning
confidence: 99%